Fish choruses from the Kimberley, seasonal and lunar links as determined by long term sea noise monitoring - McCauley, Robert (Acoustical Society of Australia, 2012)
Calling fish are a dominant component of Kimberley sea noise. Sea-noise loggers set in the Kimberley since 2004 under Industry and Defence funding have recorded a plethora of call types and choruses, where many fish call en masse. Fish choruses show daily and seasonal periodicity and most show lunar periodicity. At the longest site sampled over 2006-2010 from Scott Reef southern lagoon, a chorus produced by nocturnal planktivorous fishes displayed coupled daily, lunar and seasonal trends with calling most intense over late evening from October to April, least intense over June to August, but continuing at some level all year. This chorus is believed associated with feeding. As a comparison a near shore chorus produced by fish of the family Terapontidae is only produced over November to May, again at night. This chorus is believed associated with reproduction. As has been observed before, where multiple chorus occur each night which overlap in frequency content, time separation acts to reduce competition for the 'sound space'.